Critical Digital Literacy in English Education: Preparing Students for Information Age Communication - Nayla, Nayla; Umam, Khoirul (Bulletin of Scientific Reseach in English Education, 2025)
This study responds to the growing prevalence of misinformation in the digital era, which poses significant challenges for students’ ability to critically evaluate online information. This study aims to examine how critical digital literacy can be integrated into English language education to address these challenges. Employing a qualitative case study approach, data were collected through interviews, classroom observations, and document analysis involving English teachers. The findings indicate that integrating critical digital literacy through collaborative learning strategies enhances students’ critical thinking and communication skills, particularly in evaluating online information. This study contributes to existing literature by proposing a contextual integration model of critical digital literacy in EFL classrooms, offering practical implications for curriculum development and teacher training.